Poezja anestetyczna – nice Barbary Klickiej - Waligóra, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The paper is an attempt to analyse Barbara Klicka’s book of poetry nice, written in 2015. The interpretation is focused mainly on forms, which oscillate between prose poem and free verse. It also examines genological issues and shows main topics of presented literature, such as a revision of traditional aesthetic with an important turn into anaesthetic and its political and ethical contexts, or – in connection with philosophical, theological and social changes in the Western thought – the problem of postmodern subjectivity.